A systematic review of best practices for the perioperative management of abdominal sacrocolpopexy. Issue 5 (29th May 2020) - Nemirovsky, Amy; Herbert, Amber S.; Gorman, Emily F.; Malik, Rena D.
Abstract: Purpose: Enhanced recovery after surgery (ERAS) pathways have been shown to reduce surgical morbidity and length of stay across various procedures. Our objective was to systematically evaluate the literature for best practices of ERAS elements in abdominal sacrocolpopexy (ASC), to determine if there is sufficient evidence to create best practice guidelines for this procedure. Materials and Methods: Following the preferred reporting items for systematic review and meta‐analysis (PRISMA) statement, we performed a review using Pubmed, Embase, and Cochrane Library. Eligible articles contained ERAS components and postoperative outcomes of ASC published in English since 1997. Thirty‐five full‐text articles were selected for final qualitative analysis. Results: Poor functional status before ASC was associated with a longer length of hospital stay. Laparoscopic ASC was associated with a shorter postoperative hospital stay, with no difference between laparoscopic and robotic approaches. Epidural analgesia in addition to spinal anesthesia lowered levels of pain throughout the postoperative stay in laparoscopic ASC. A multimodal bowel regimen shortened time to first bowel movement compared to a single agent regimen. Removing a Foley catheter may lead to sooner first spontaneous void but may result in higher rates of urinary retention and urinary tract infection. Studies investigating preoperative bowel preparation, preanesthesia medication, and multidose antimicrobial prophylaxis did not show significant benefit. Conclusions: Best practices for ASC can be developed based on current findings from the literature and extrapolation of evidence from other surgeries where ASC‐specific elements are missing, with the ability to modify the pathways as new data become available.